Opportunity & participation for women mine workers in the Bolivian Altiplano : a thesis presented in partial fulfilment of the requirements for the degree of Master of Philosophy in Development Studies at Massey University, Manawatu campus, New Zealand - Markland, Howard R. (Massey University, 2012)
Despite the range of research into mines and mining communities in the Bolivian Altiplano over the last 40 years, little attention has been paid to the role of women, despite their significant involvement in the sector for 500 years. Researchers have also tended to focus upon large, State mining operations, although in the last decade there has been growing interest in artisanal mine worker co-operatives, typically in the Department of Potosi. Bolivia’s 1952 socialist revolution significantly improved State sector opportunities for women in the mining sector, but many were made redundant following the 1985 Tin Crisis. Displaced workers subsequently joined artisanal mine worker co-operatives, where most earned a subsistence living by recovering mineral residues from waste rock, tailings piles and alluvial deposits, while few worked in underground roles. This research aimed to characterise the current participation of women workers in the Altiplano mining sector, focusing upon artisanal tin mining activities in the Department of Oruro. The research methodology involved a combination of literature review and in-country data collection, with visits to 19 mine sites and interviews with 27 stakeholders representing a diverse range of sector interests. Women mine workers in Bolivia are widely referred to using the collective term Palliris, although women involved in mining and reprocessing work perform at least 10 distinct occupational roles, each with its own title. Their participation in the mining sector has declined dramatically in the last decade, despite unprecedented access to employment opportunities and record tin prices. Indeed, women workers have all but disappeared from many Altiplano mine sites. These conclusions challenge recent research and official statistics, both of which indicate a sustained increase in female participation in artisanal mining. The principal reasons for declining female participation are considered to be: declining mineral content of waste rock and tailings piles; more attractive employment opportunities outside the sector; and an overall decline in mining sector employment. It was also noted that female participation is likely to continue declining, as mining sector production is rapidly becoming dominated by large scale, mechanised operations, that have no need for labourers with artisanal mining skills.
Keywords: Mining, Bolivia; Tin mining; Women miners, Bolivia; Artisanal mine workers; Women mine workers